2022
DOI: 10.3390/drones6100279
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Volume Calculation and Mapping of Construction and Demolition Debris Using Drones, Deep Learning, and GIS

Abstract: This paper presents a time- and cost-efficient method for the management of construction and demolition (C&D) debris at construction sites, demolition jobsites, and illegal C&D waste dumping sites. The developed method integrates various drone, deep learning, and geographic information system (GIS) technologies, including C&D debris drone scanning, 3D reconstruction with structure from motion (SfM), image segmentation with fully convolutional network (FCN), and C&D debris information management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Another is to compute the volumes of C&D waste in landfills by applying mobile mapping technology provided by GeoSLAM (Simultaneous localisation and mapping) [18]. A study demonstrates that an innovative approach effectively integrates various technologies, such as Drones, CV, GIS, and 3DR, which shows better results in the final quantification and mapping of C&D debris [19]. Big Data (BD) is adopted in C&D waste management to analyse massive amounts of information generated from C&D waste to settle landfill management issues [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another is to compute the volumes of C&D waste in landfills by applying mobile mapping technology provided by GeoSLAM (Simultaneous localisation and mapping) [18]. A study demonstrates that an innovative approach effectively integrates various technologies, such as Drones, CV, GIS, and 3DR, which shows better results in the final quantification and mapping of C&D debris [19]. Big Data (BD) is adopted in C&D waste management to analyse massive amounts of information generated from C&D waste to settle landfill management issues [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Considering the criteria that those with a minimum number of citations equal to 50 are relevant authors in the field under study, 12 authors, divided into two clusters, were identified (see Figure 6). Of these, seven authors, namely Zhang, H., Li, S., Wang, Y., Li, Y., Wang, X., Zhang, X., and Solla, M., hold the authorship of documents included in the set under analysis (84 documents), including five articles considered in Phases 4 and 5 [30,[38][39][40][41]. Upon analyzing Figures 2-6, it becomes evident that the number of scientific publications related to the use of UAVs for infrastructure inspection and monitoring, as well as the emergence of relevant authors in this field, are on a rising trend.…”
Section: Characterization Of the Selected Documentsmentioning
confidence: 99%
“…This progress stands out as a crucial element for the effective understanding and monitoring of infrastructures, including those related to transportation [20,21,23]. This technology has been comprehensively applied to the monitoring and management of construction works [41,44], including those related to road construction [45], and in the management of transport infrastructure assets, such as pavements. Application studies aimed at monitoring [7][8][9]12,13,46,47] and determining [26] the condition of flexible road pavements are common, with less expression for rigid [47], stone [28], or airport [7,17] pavements.…”
Section: Research Trend Analysismentioning
confidence: 99%
“…Shape and position control in concrete casting and precast installation requires finding accurate object/segment boundaries [7]. Volume calculations in the construction and demolition (C&D) phases can be automated from laser scanner, UAV, or satellite syn-thetic aperture radar (SAR) footage with the help of semantic segmentation [8,9]. Reverse engineering digital twins of existing buildings (as built and scan to BIM) requires assigning element classes to scan data to reconstruct element geometries [10,11].…”
Section: Introductionmentioning
confidence: 99%